Dynamics of Making of Large Dam: An overview of Benefits and Challenges - Bhagat, Santosh K. (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
Worldwide debate concerning large dam is remarkably a complex issue in development field. It becomes more complex because the issue is not only confined to planning, designing, and development of dams but also embraces a series of social, cultural and environmental aspects besides human being’s desire and aspiration of progress. It is obvious that large dams are constructed to generate numerous benefits such as hydropower electricity, irrigation and flood control, increased water supply that eventually brings comprehensive benefits to the society, culture and nation as a whole. In the pursuit of development of Nepal, it is an established fact that hydropower remains the most important resource which has a huge potential to contribute for the energy demand as well as a better social and economic status of its citizen that ultimately lead to accelerate the economic growth of the country. Nepal has received tremendous support from many developed countries and various institutions for the construction of large dam with a purpose of producing hydropower. This paper seeks to analyze the various aspects and impacts of large dam construction with reference to the displacement and resettlement of the evicted people.